Cytokines in CAR T Cell–Associated Neurotoxicity - Gust, Juliane; Ponce, Rafael; Liles, W. Conrad; Garden, Gwenn A.; Turtle, Cameron J. (Frontiers in Immunology, 2020)
Chimeric antigen receptor (CAR) T cells provide new therapeutic options for patients with relapsed/refractory hematologic malignancies. However, neurotoxicity is a frequent, and potentially fatal, complication. The spectrum of manifestations ranges from delirium and language dysfunction to seizures, coma, and fatal cerebral edema. This novel syndrome has been designated Immune effector Cell Associated Neurotoxicity Syndrome (ICANS). In this review, we draw an arc from our current understanding of how systemic and potentially local cytokine release act on the CNS, toward possible preventive and therapeutic approaches. We systematically review reported correlations of secreted inflammatory mediators in the serum/plasma and cerebrospinal fluid with the risk of ICANS in patients receiving CAR T cell therapy. Possible pathophysiologic impacts on the CNS are covered in detail for the most promising candidate cytokines, including IL-1, IL-6, IL-15, and GM-CSF. To provide insight into possible final common pathways of CNS inflammation, we place ICANS into the context of other systemic inflammatory conditions that are associated with neurologic dysfunction, including sepsis-associated encephalopathy, cerebral malaria, thrombotic microangiopathy, CNS infections, and hepatic encephalopathy. We then review in detail what is known about systemic cytokine interaction with components of the neurovascular unit, including endothelial cells, pericytes, and astrocytes, and how microglia and neurons respond to systemic inflammatory challenges. Current therapeutic approaches, including corticosteroids and blockade of IL-1 and IL-6 signaling, are reviewed in the context of what is known about the role of cytokines in ICANS. Throughout, we point out gaps in knowledge and possible new approaches for the investigation of the mechanism, prevention, and treatment of ICANS.